Smart molecular crystal switches - Hou, Ian Cheng‐Yi (2024)
The multifaceted switches are part of our everyday life from the macroscopic to the molecular world. A molecular switch operating in the solution and in the crystalline state is very different. In this review, we summarize the state‐of‐the‐art of smart molecular crystal switches based on molecular martensites. These crystal switches respond to external stimuli and reversibly change between states, retaining their macroscopic integrity. The operation of the switches predominantly relies on temperature alterations or mechanical stress, with emerging methods based on photothermal effects, photoisomerization, and host‐guest chemistry. The capability of changing the molecular orientation and interaction in smart molecular crystal switches offers opportunities in several applications, including actuators, reversibly shaping structural materials, optoelectronic and magnetic materials, as well as switchable porous materials. Smart molecular crystal switches have vast potential in modern scientific and technological progress. The ongoing research shapes a rich landscape for innovation and future scientific exploration across diverse disciplines.